A Comparison Study of Moving Object Index Structures - Kalay, Utku; Kalipsiz, Oya (SCIENCE PRESS, 2009)
The task of selecting the most appropriate method for indexing the data according to application requires a careful comparison study of indices of interests. In particular, we consider object movements by tracing their trajectories within a predefined road network. MV3DR-tree and 3DR-tree constitute our first group indexing the objects moving in free movement scenarios. Besides, Mapping and MON-tree are the second group indexing the locations of objects moving over a network of road. Those access methods mainly organize a group of R-tree in order to index the underlying road network and the object movements. Our goal in this study is to evaluate existing proposals under fair circumstances with respect to storage consumption and spatio-temporal query execution performance. In our comparisons, we discuss the structure's sensibility to query's spatial and/or temporal extent as well as the tradeoff arising between two groups in terms of reliability and disk access performance. We believe that revealing the vulnerabilities of the selected structures, especially Mapping and MON-tree motivates us to design more robust organizations.
Keywords: access methods; query processing; spatial databases; temporal databases; Computer Science